Candidate Selection in Canada: Local Autonomy, Centralization, and Competing Democratic Norms. (June 2016) - Pruysers, Scott; Cross, William
This article examines how political parties choose their candidates in Canada's decentralized multilevel setting. We examine the selection practices of the leading federal parties, focusing on the formal and informal rules relating to the eligibility and mobilization of voters and candidates, the distribution of power within the party, and representational outcomes. In doing so, we highlight how Canadian parties have approached the trade-off between competing democratic norms as each party attempts to find a delicate balance between grassroots authority and central party involvement. Despite typically being considered a local affair, the selection of candidates is highly influenced by the central party apparatus—both formally and informally. This central party authority, however, often results in considerable tension that erupts in public conflict. We suggest that while centralization may undermine membership participation, grassroots autonomy, and responsiveness, central party involvement may also enhance the democratic values of fairness, representation, and in some instances even participation.